Major ion concentrations in spring water across Main Central Thrust in central Nepal - Sapkota, Soma Nath; Perrier, Frédéric (Journal of Nepal Geological Society, 2012)
Thirteen springs were sampled across the Main Central Thrust (MCT) in the vicinity of Syaule in central Nepal, where schists and gneisses from the Higher Himalayan Crystallines are carried over phyllites and slates interbedded with calcareous bands of the Lesser Himalaya. The spring water from the carbonate units is characterised by a higher electrical conductivity and a higher temperature (around 20 °C). The water geochemistry is dominated by calcium and magnesium carbonates with electrical conductivity as well as calcium, magnesium, and sulphate concentrations proportional basically to alkalinity. The springs with a lower conductivity and temperature are associated with a higher (Na+K)/(Ca+Mg) concentration ratio indicating the predominance of silicate alteration. The electrical conductivity, temperature, and ion concentrations show a remarkable spatial distribution with an overall decrease of conductivity from south to north associated with an unambiguous increase of (Na+K)/(Ca+Mg) concentration ratio when entering the Higher Himalayan Crystallines. The spring at the MCT is characterised by a (Na+K)/(Ca+Mg) concentration ratio of larger than 5. The electrical conductivity and temperature also exhibit increasing trends with rising altitude, which could be representative of larger-scale patterns controlled by the Himalayan geology. In terms of its alkalinity and (Na+K)/(Ca+Mg) concentration ratio, the Syaule water sample is clearly separated from the hot springs of central Nepal or other geothermal springs (e.g., in Turkey or France), which are characterized by a higher conductivity and a greater (Na+K)/(Ca+Mg) concentration ratio. The Syaule sample also bridges the gap between the spring waters representative of a gneiss–metasediments contact in the French Alps and the various thermal springs representative of the andesitic La Soufriere volcano of La Guadeloupe. The spatially coherent Syaule spring water can provide information on large-scale fluid circulation in active tectonic settings and define the baseline for the search of anomalous springs where signatures of geodynamic phenomena, such as possible earthquake precursors, might be observed. Jour. Nep. Geol. Soc., Vol. 37, 2008, 55-56